The Plant Protection Capabilities of Extension Workers in Enhancing Maize (Zea mays L.) Production: A case study of District Shangla Khyber Pakhtunkhwa, Pakistan (Research and Social Study Institute, 2022)
This study analyzed farmers’ perceptions about plant protection capabilities of extension workers in enhancing maize production in remote District Shangla Khyber Pakhtunkhwa-Pakistan. Educating farmers about modern technologies of crops is the mandate of the extension staff of the provincial agriculture extension department. For this research, two villages were taken purposively from three union councils of Tehsil Besham of District Shangla for data collection through a well-structured interview schedule. A total of 204 farmers were selected for data collection, which was analyzed using SPSS V.20 software. Descriptive statistics, 5 points Likert scale, and Chi-square tests were used. About 32% of respondents were found in the age 26-35 years, 46.6% respondents have 1-2 acres of land under maize crop while 57.8% maize growers were literate with 20.1% respondents educated up to matric. Maximum (82.4%) growers were getting 6400-12800 kg/acre maize production by cultivating local varieties. Awareness about alternative pest management technique was ranked 1st with the highest mean value of 3.04 and standard deviation of 1.13, and performing pest monitoring on maize were ranked 2nd with a mean value of 2.84 and standard deviation of 1.14. In contrast, identifying symptoms of major insects/pest diseases was ranked 5th with the lowest mean value of 2.67 and a standard deviation of 1.23. Their plant protection issues by educating them on disease-resistant varieties and weather suitability of maize hybrid varieties for higher production through local agriculture programs broadcasted on a local FM channel and pamphlets.